Pre-settlement small pelagic larvae in Ambon Bay based on length distribution - Grace Hutubessy (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2022)
Larval occurrence in Ambon Bay is related to the larval settlement and indirectly affects the population of pelagic species which have nursery ground in Ambon Bay. The objective of this study is to analyze the factors that influence larval fish occurrence in Ambon Bay based on the length distribution. A lift net assisted by 6 LED lights was operated during the dark to catch larval fish and data was collected from 2016-2018 at Hative Besar, Ambon City. Length frequency with a 5 mm interval was set following the sampling dates. Two variables: length frequency and the number of new individuals (<20mm) together with information on tides and moon phase obtained from the website were collected for further analysis. The larval occurrence was associated with 4 moon phases (dark, first quarter, full and third quarter) and with 2 types of tides: semi-diurnal and mixed semi-diurnal. The normality test (Kolmogorov–Smirnov test) showed normal distribution on length data and the ANOVA showed no significant difference in larval occurrence among the moon phases (F=1.223, P=0.318) but between semi-diurnal and mixed semi-diurnal, and larval recruitment was significantly different (F=3.07; P=0.003), small size larvae were abundance during semi-diurnal tides while large larvae during mixed semi-diurnal tides. It is concluded that small pelagic larval occurred throughout the year and the new cohort occurred by the influence of the tidal current to Ambon bay. Our findings highlight the biological impacts of lift net siru-siru as priorities for the management of fisheries in Ambon bay. Abstrak Pola kehadiran larva ikan di Teluk Ambon berkaitan erat dengan proses menetap dan secara tidak langsung berkaitan juga dengan dinamika populasi ikan pelagis yang memilih daerah pembesaran di dalam Teluk Ambon. Penelitian ini bertujuan untuk menganalisis faktor lingkungan yang memengaruhi kehadiran pra-menetap larva ikan pelagis kecilberdasarkan frekuensi panjang. Larva ikan ditangkap dengan menggunakan siru-siru dengan bantuan lampu di malam hari. Sampling dilaksanakan dari tahun 2016 hingga 2018 di Negeri Hative Besar, Ambon. Frekuensi panjang total larva ditabulasi dalam bentuk histogram dengan kisaran 5 mm untuk setiap tanggal sampling. Dua variabel: panjang dan jumlah individu baru (≤ 20mm) bersama dengan hari bulan dan pasang surut digunakan untuk analisis selanjutnya. Kehadiran larva dihubungkan dengan hari bulan (4 fase: bulan baru, kwartir pertama, purnama dan kwartir terakhir) dan tipe pasang surut (harian ganda dan tipe campuran). Uji normalitas Kolmogorov–Smirnov test menunjukkan sebaran data panjang normal (P=0.20). Selanjutnya hasil ANOVA menunjukkan kehadiran pra-menetap larva di Teluk Ambon tidak dipengaruhi hari bulan (F=1,223, P=0,318), tetapi dipengaruhi oleh pasang surut (F=3,07; P=0,003) ketika larva berukuran kecil lebih banyak tertangkap pada tipe harian ganda, sedangkan larva yang lebih besar pada tipe campuran. Kehadiran pra-menetap larva ikan pelagis kecil terjadi sepanjang tahun dan kehadiran individu baru di Teluk Ambon dipengaruhi oleh arus pasang surut. Hasil penelitian ini menyorot dampak biologis dari perikanan siru-siru sebagai prioritas pengelolaan perikanan di Teluk Ambon.